2015
DOI: 10.1016/j.brainres.2015.07.054
|View full text |Cite
|
Sign up to set email alerts
|

P50: A candidate ERP biomarker of prodromal Alzheimer׳s disease

Abstract: INTRODUCTION Reductions of cerebrospinal fluid (CSF) amyloid-beta (Aβ42) and elevated phosphorylated-tau (p-Tau) reflect in vivo Alzheimer’s disease (AD) pathology and show utility in predicting conversion from mild cognitive impairment (MCI) to dementia. We investigated the P50 event-related potential component as a noninvasive biomarker of AD pathology in non-demented elderly. METHODS 36 MCI patients were stratified into amyloid positive (MCI-AD, n=17) and negative (MCI-Other, n=19) groups using CSF levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 34 publications
3
20
0
1
Order By: Relevance
“…Our results suggest that a very early stage of alteration in auditory gating processing is associated with an absence of mPFC gating transmission that corrupts habituation to redundant inputs [Josef Golubic et al, 2014a]. The impaired mPFC processing during endogenous brain activity or during memory tasks in cognitively normal participants who were AD risk-factor gene (APOE E 4) carriers together with evidence of reduced gating amplitude as a predictor of cerebrospinal amyloid-b reduction in MCI patients [Green et al, 2015] strongly support our speculation that absent mPFC gatingout activation in lower functioning controls may be associated with a possible preclinical AD phase. Also, it has been shown that PFC structures are affected by taupathology in the possible preclinical stage of AD [Giannakopoulos et al, 2007].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our results suggest that a very early stage of alteration in auditory gating processing is associated with an absence of mPFC gating transmission that corrupts habituation to redundant inputs [Josef Golubic et al, 2014a]. The impaired mPFC processing during endogenous brain activity or during memory tasks in cognitively normal participants who were AD risk-factor gene (APOE E 4) carriers together with evidence of reduced gating amplitude as a predictor of cerebrospinal amyloid-b reduction in MCI patients [Green et al, 2015] strongly support our speculation that absent mPFC gatingout activation in lower functioning controls may be associated with a possible preclinical AD phase. Also, it has been shown that PFC structures are affected by taupathology in the possible preclinical stage of AD [Giannakopoulos et al, 2007].…”
Section: Discussionmentioning
confidence: 92%
“…A range of EEG/MEG studies, measuring spontaneous and/or evoked brain activity, have reported changes in neural processing that correlate with the neuropathology of symptomatic AD [Bajo et al, ; Cheng et al, ; Golob et al, ; Green et al, ; Irimajiri et al, ; Jelic et al, ; Maestú et al, ; Stephen et al, ; Stam et al, ; Thomas et al, ]. Particularly, neurophysiological studies have found differences in early processing of auditory [Cheng et al, ; Green et al, ; Irimajiri et al, ; Thomas et al, ] and somatosensory stimuli [Stephen et al, ] in MCI/AD patients, affirming the possibility of impaired inhibition of redundant stimuli (gating‐out) and processing of distracting stimuli (gating‐in) in the initial phase of symptomatic AD. In addition, increased power in delta and theta bands, accompanied by a loss of resting‐state functional connectivity in lower alpha and beta bands have been detected in AD patients [Stam et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Our early positive deflection in the time range of the P50 matches the results found in previous studies in which the P50 is altered in MCI and AD. The enhanced P50 response is well described in patients with AD and MCI (Green et al ., ). Another study compared amnestic MCI patients treated with cholinesterase inhibitors to untreated patients and found larger P50 amplitudes in untreated patients with MCI (Irimajiri et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Quantitative magnetic resonance imaging (MRI) revealed normal hippocampal size and lateral ventricle volume but confluent white matter hyperintensities with frontal lobe predominance. Auditory event–related potentials demonstrated slow median reaction times and low amplitude at the N200 peak (linked to impaired attention and executive function) and left–right asymmetry with frontal predominance (linked to vascular injury) but normal amplitudes and latencies at all other peaks, including the P50 peak associated with amyloid deposition . This deep phenotypic evaluation provided findings in cognitive testing (executive and working memory deficits with cued episodic memory improvements supporting intact hippocampal circuitry), physical testing (sarcopenia, at‐risk nutritional status, poor physical functionality, and early frailty), gait testing (slowed gait speed, impaired dual tasks, postural instability with eyes closed), biomarker testing (lipid profile, inflammation, insulin resistance, ApoE4 genotype suggesting poor response to statins), MRI (preservation of hippocampal and cortical volume, extensive white matter disease), and electroencephalography (executive dysfunction and evidence of vascular injury) that could be treated and supported a diagnosis of vascular cognitive impairment.…”
Section: Example Of a Personalized Medicine Approach To Dementia Prevmentioning
confidence: 92%
“…Auditory event-related potentials demonstrated slow median reaction times and low amplitude at the N200 peak (linked to impaired attention and executive function) and left-right asymmetry with frontal predominance (linked to vascular injury) but normal amplitudes and latencies at all other peaks, including the P50 peak associated with amyloid deposition. 30 This deep phenotypic evaluation provided findings in cognitive testing (executive and working memory deficits with cued episodic memory improvements supporting intact hippocampal circuitry), physical testing (sarcopenia, at-risk nutritional status, poor physical functionality, and early frailty), gait testing (slowed gait speed, impaired dual tasks, postural instability with eyes closed), biomarker testing (lipid profile, inflammation, insulin resistance, ApoE4 genotype suggesting poor response to statins), MRI (preservation of hippocampal and cortical volume, extensive white matter disease), and electroencephalography (executive dysfunction and evidence of vascular injury) that could be treated and supported a diagnosis of vascular cognitive impairment. A personalized treatment plan was then developed focusing on dietary counseling (Mediterranean-DASH Intervention for Neurodegenerative Delay diet, high-protein snacks, glycemic control); physical therapy for gait, balance, strengthening, and conditioning; referral to a personal trainer for aerobic, resistance, and flexibility training; mindfulness (yoga, meditation) for stress reduction; cognitive exercise focusing on problem-solving skills; omega-3 supplementation and possible resin therapy for cholesterol lowering; better blood pressure monitoring; and initiation of low-dose aspirin to improve blood flow.…”
Section: Example Of a Personalized Medicine Approach To Dementia Prevmentioning
confidence: 99%